Perkawinan Sesuku pada Masyarakat Minangkabau di Kecamatan Basa Ampek Balai Tapan Kabupaten Pesisir Selatan - Angel Lova, Fivhry; Amir, Diana; Manik, Herlina (Universitas Jambi, Fakultas Hukum, 2026)
This study aims to determine and analyze the prohibition of inter-tribal marriage in the Minangkabau community in Basa Ampek District, Balai Tapan of South Pesisir Regency. The formulation of the problem in this study is: 1) What are the forms of customary sanctions against tribal marriage in Basa Ampek District, Balai Tapan South Coast Regency 2) How effective is customary sanctions on interfaith marriage in Basa Ampek District, Balai Tapan South Pesisir Regency. This study uses an Empirical Juridical approach with primary data obtained through interviews and secondary data obtained from literature studies. The results of the data are processed using qualitative methods. The results of the study found that the form of customary sanctions given to tribal marriage perpetrators is to pay customary fines, slaughter the white kabau saikua, be banished throughout the tribe, and be expelled from the nagari. In this day and age, the existence of customary sanctions has not been able to erase the occurrence of the practice of intertribal marriage in Basa Ampek District, Balai Tapan, South Pesisir Regency.